SOCIAL SHYNESS AND ITS RELATIONSHIP TO POOR CLASSROOM PARTICIPATION IN FEMALE SECONDARY STUDENTS - Saif Muhammad Jassim Al-Maliki (American Journals Publishing, 2025)
and preparatory female students of Al-Kawthar Girls' High School in Qurna District, Basra, and revealing the relationship between social shyness and the level of participation. To achieve these aims, a measure of social shyness has been developed based on Zimbardo's (1977) theory of social shyness, taking into account certain components of the theory, including the psychological component, the physiological component, the cognitive component, and the emotional component. Therefore, the scale in its final form included 22 items across the components. Alternative replies have been assigned five options: always apply - often apply - sometimes apply - rarely apply - never apply. Scores were given between (5-1), thus ranging from a total scale score (110-22) to a hypothetical average score of (66). The final application procedure for the scale was conducted on 100 respondents from 24/10/2023 to 30/10/2023. The how-to-answer instructions and the research aims were explained. The required data on social shyness and class participation were obtained from the respondents in collaboration with the distinguished school administration. After obtaining a class participation score for the sample and statistically processing data using Spearman's correlation coefficient and T-test, the study found that after achieving the first aim, which is uncovering the level of social shyness, the mean and standard deviation were used. The mean is (84), the standard deviation is (6.3), and the hypothetical mean is (66). Using the T-test equation on the respondents' replies, the calculated T-test value was 0.0077 and the tabulated T-test value was 1.96. To achieve the second aim, which is revealing the relationship between social shyness and female students' participation, Spearman's correlation coefficient was used to calculate female students' grades on the scale of social shyness and their degrees in difficult participation. The correlation coefficient amounted to (0.0077), which means that there is a correlation between social shyness and class participation and that shyness negatively affects class participation. Additionally, data analysis found that 60% of female students show a lower class participation due to social shyness.
Keywords: Social Shyness, Relationship, Classroom, Participation, secondary Students,